DEVELOPMENT STRATEGY OF AGRICULTURAL SECTOR FOR SUPPORT THE ECONOMY ACTIVITIES IN BORDER AREAS OF WEST KALIMANTAN - Imelda, Imelda (Universitas Brawijaya, Indonesia, 2018)
The purpose of this study is to identify development strategy of the agricultural sector for supportthe economic activities in border areas of West Kalimantan. The research location in Badau District with consideration of the first line border area in Kapuas Hulu andas a national strategic activity area. Research data is sourced from primary data and secondary data. Primary data include internal and external variables affecting agricultural activities in the border area of Kapuas Hulu Regency. Data analysis using SWOT and QSPM. The SWOT analysis shows that the development of border agricultural sector in Badau District is in the area of V (concentration strategy by applying horizontal integration or stability) meaning that the development of the agricultural sector in the border area of West Kalimantan should be concentrated on utilizing the strength and growth opportunities of the region. The QSPM analysis concludes that the first strategic priority is the empowerment of farmers in the application of technology in cultivation, harvest, and postharvest activities.